Solid-liquid filtration : practical guides in chemical engineering - Perlmutter, Barry A. (Elsevier Ltd., 2015)
Annotation "Practical Guides in Chemical Engineering" are a cluster of short texts that each provides a focused introductory view on a single subject. The full library spans the main topics in the chemical process industries that engineering professionals require a basic understanding of. They are pocket publications that the professional engineer can easily carry with them or access electronically while working. Each text is highly practical and applied, and presents first principles for engineers who need to get up to speed in a new area fast. The focused facts provided in each guide will help you converse with experts in the field, attempt your own initial troubleshooting, check calculations, and solve rudimentary problems."Solid-Liquid Filtration" covers the basic principles and mechanisms of filtration, filtration testing including filter aids and filter media, types of filtration systems, selection of filtration systems and typical operating and troubleshooting approaches. This guide alsodiscussesgeneral applications and tips for process filtration and can be utilized by process engineers as a framework for idea-generation when analyzing filtration for an operating bottleneck issue or a new process development problem. Practical, short, concise information on the basics will help you get an answer or teach yourself a new topic quicklySupported by industry examples to help you solve a real world problemSingle subject volumes provide key facts for professionals."
Keywords: Filters and filtration.; elektronické knihy; electronic books